Colonization characteristics of fungi in Polygonum hydropipe L. and Polygonum lapathifolium L. and its effect on the content of active ingredients - Zhang, Xiaorui; Lv, Hongyang; Tian, Maoying; Dong, Zhaowei; Fu, Qinwen; Sun, Jilin; Huang, Qinwan; Wang, Jin (Frontiers in Plant Science, 2022)
P. hydropiper is a plant of the Persicaria genus, is commonly used to treat various diseases, including gastrointestinal disorders, neurological disorders, inflammation, and diarrhea. However, since different local standards of P. hydropiper, people often confuse it with Polygonum lapathifolium L. and other closely related plants. This poses a serious threat to the safety and efficacy of the clinical use of P. hydropiper. This study determined the six active ingredients of P. hydropiper and P. lapathifolium, and the endophytic fungi of the two group samples were sequenced using Illumina Miseq PE3000. The results showed significant differences between the community composition of the leaves, stems and roots of the P. hydropiper and the P. lapathifolium under the same soil environment. Of the 6 secondary metabolites detected, 5 had significant differences between P. hydropiper and P. lapathifolium. Then we evaluated the composition of the significantly different community between the P. hydropiper and the P. lapathifolium. In the P. hydropiper, the relative abundance of differential community in the leaves was highest, of which Cercospora dominated the differential community of the leaf and stem; In the P. lapathifolium, the relatvie abundance of differential community in the stem was highest, and Cladosporium dominated the differential community in the three compartments. By constructing the interaction network of P. hydropiper and P. lapathifolium, and characterizing the network nodes, it was found that the core community in the P. hydropiper accounted for 87.59% of the total community, dominated by Cercospora; The core community of P. lapathifolium accounted for 19.81% of the total community, dominated by Sarocladium. Of these core communities, 23 were significantly associated with active ingredient content. Therefore, we believe that the community from Cercospora significantly interferes with recruiting fungal communities in the P. hydropiper and affects the accumulation of secondary metabolites in the host plant. These results provide an important foundation for the large-scale production of P. hydropiper, and indicate that by colonizing specific fungal communities, secondary metabolic characteristics of host plants can be helped to be shaped, which is an essential means for the development of new medicinal plants.